PENGARUH PENAMBAHAN MAGGOT SEGAR TERHADAP KUALITAS TELUR ITIK MOJOSARI PADA FASE PUNCAK PRODUKSI HINGGA LAYER II: THE EFFECT OF THE ADDITION OF FRESH MAGGOT ON MOJOSARI DUCK EGG QUALITY PEAK PHASE PRODUCTION UP TO LAYER II - Wiyanjana, Mahanani Ilham Denta; Purwadi, Purwadi; Wulandari, Eudia Christina (Universitas Boyolali, 2024)
The aim of this research was to determine the effect of adding fresh maggots as an alternative feed on the quality of laying duck eggs. The material used was 60 laying ducks aged 28 weeks. The treatment was as follows: (T0 = 100% finished feed), (T1 = 5% fresh maggot + 100% finished feed), (T2 = 10% fresh maggot + 100% feed finished), (T3 = 15% fresh maggot + 100% finished feed). The parameters observed were: feed consumption, daily duck productivity, shell thickness, egg weight and shell weight. If the results of the analysis have a significant impact, then proceed with the Duncan's distance test. The results of the analysis showed that it had a real effect on feed consumption but had no real effect on daily duck productivity, shell thickness, egg weight and shell weight